PRINSIP KEMANDIRIAN EKONOMI PERSPEKTIF RASULULLAH - Imron Rosadi; Lutfiyanto (Sekolah Tinggi Ilmu Ekonomi Bakti Bangsa, 2025)
Rasulullah is a leader of the ummah throughout the world, where he is a role model in worship, social interaction with others or in doing charity, because everything that originates from Rasulullah is sunnah in accordance with what was conveyed by hadith scholars, which means